Discourse and Agency during Scaffolded Middle School Science Instruction. Issue 5 (3rd July 2022) - Lombardi, Doug; Matewos, Ananya M.; Jaffe, Joshua; Zohery, Vivian; Mohan, Svetha; Bock, Kellyann; Jamani, Sonia
ABSTRACT: Instructional scaffolds may promote science learning, particularly for topics that are controversial. Scaffolding may also need to be autonomy supportive, particularly for adolescents, and designed to facilitate scientific discourse and agency. The purpose of the present study was to investigate differences in middle school students' discourse and agency across two scaffold forms: one more autonomy-supportive and one less autonomy-supportive. We designed both to facilitate scientific evaluations about the connections between lines of evidence and alternative explanations about two geological phenomena: relations between hydraulic fracturing and earthquakes (less autonomy-supportive) and reliability of fossil evidence for inferring past surface changes (more autonomy-supportive). Integration of qualitative and quantitative findings revealed meaningful differences, with greater collective disciplinary agency expressed during the more autonomy-supportive form. Results support a burgeoning area of research suggesting that productive discourse and agency are necessary to prepare students to participate in a civically minded and inclusive society.